Comparative Safety and Efficacy of Left Atrial Appendage Occlusion with the Watchman Device and Amplatzer Cardiac Plug: Results of the Russian National Registry. (9th November 2020) - Davtyan, Karapet; Simonyan, Georgiy; Topchyan, Arpi; Kalemberg, Andrey; Romanov, Alexander; Shabanov, Vitaliy; Lebedev, Dmitriy; Gureev, Sergey; Miller, Yulia; Merkulov, Evgeniy; Pevzner, Dmitry; Mozgovoy, Pavel; et al.
Abstract : Purpose . This multicenter, prospective registry evaluated the comparative safety and efficacy of left atrial appendage occlusion (LAAO) using the Watchman device (WD) and the Amplatzer Cardiac Plug (ACP) in patients with nonvalvular atrial fibrillation (NVAF) in real-world clinical practice in Russia. Methods . The study included data from 200 consecutive NVAF patients (66.8 ± 7.8 years, 44.5% female, median CHA2DS2VASc 4, median HAS-BLED 3) who had undergone LAAO implantation using WD (n = 108 ) or ACP (n = 92 ) from September 2015 to December 2017 in 5 medical centers in Russia. The primary safety endpoint was the procedure-related major adverse events, and the primary efficacy endpoint was the composite of thromboembolic events, device thrombosis, hemorrhagic events, and unexplained death during the 12-month follow-up. Results . Successful LAAO was performed in all 92 (100%) patients with ACP and 105 (97.2%) with WD (p = 0.053 ). At 12 months, primary safety endpoint occurred in 6.5% of patients in the ACP group with no events in the WD group (6.5% vs. 0%, p = 0.008 ). During the 12-month follow-up, the primary efficacy endpoint has occurred in 8.3% of patients in the WD group (n = 9 ) and 1.1% of patients in the ACP group (n = 1 ) (p = 0.016 ). Conclusions . In this multicenter prospective registry, LAA closure with the WD was associated with significantly higher thromboembolic events rate in NVAF patients. Patients, receiving the ACP, had more procedure-related major adverse events. However, further multicenter studies are necessary to evaluate these findings.